Dissolution of mixed oxide(MOX) fuel in nitric acid:A review - Tianchi Li; Fang Liu; Zhou Jia; Fangxiang Luo; Taihong Yan; Weifang Zheng (Heliyon, 2024)
The fast neutron reactor is an internationally promising fourth-generation reactor. The main fuel for this reactor is a mixed oxide fuel, and its reprocessing is currently one of the technical challenges being tackled by various countries. One of the difficulties in the reprocessing of mixed oxide (MOX) fuel lies in the nitric acid dissolution process. The high Pu content in MOX fuel can lead to issues such as solvent radiolysis, nuclear criticality, increased insoluble residues, and slow dissolution rates during the nitric acid dissolution process. These challenges have yet to be effectively addressed. This article discusses the chemical aspects of nitric acid dissolution of MOX fuel and investigates the impact of fuel manufacturing processes, the addition of metal catalyst ions, hydrofluoric acid addition, fuel plutonium content, dissolution temperature, and ultrasonic assistance on the nitric acid dissolution of MOX fuel. A review of various countries' engineering practices related to MOX fuel dissolution is presented. Based on the research findings and experiences, a potentially feasible future industrial processing route for MOX fuel is proposed, and future research priorities are outlined.